Chemical analysis of buffalo meat in a self-consumption system in northeastern of Argentina - Gladis Rébak; Gladys Obregón; Diego Gómez; Laura Vázquez-Acosta; Mariano Pino; Julia Obregón; Rosa Molina; Victoria Cantero; Luz Segovia-Espinola (Revista Científica)
The Argentine Northeast region is characterized by its subtropical climate, with low and floodable land with significant environmental variability. The exploitation of buffaloes is presented as an alternative for meat production, as it adapts to special agro-ecological conditions due to waterlogging of the land, the presence of low-digestibility pastures and ectoparasites in which beef cattle do not always express their maximum potential. This research was carried out as part of a larger work at the El Carmen farm, 20 km from Corrientes, which has approximately 30 hectares, where beef cattle and buffaloes coexist. The sample included 15 post-weaning Murrah (n: 5), Mediterranean (n: 5) buffaloes breeds and their crosses (n: 5), with ages ranging from 12 to 15 months and average weights of 380 kg. Animals were raised on natural fields, with access to self-consumption hoppers to supply food composed of alfalfa bales, broken and whole corn, and soybean pellets with a consumption of 1.5% of live weight. The composition of the food supplied as strategic supplementation to achieve the slaughter weight was studied, as well as the chemical composition of the meat, taking samples of the Longissimus dorsi muscle between the 11th and 13th ribs, obtaining steaks with a thickness of 2.5 cm., being conditioned in bags of first use and refrigerated at 4 ºC until its processing in the laboratory of the Food Technology Service of the Faculty of Veterinary Sciences of Corrientes. With the steak samples (n: 15), we determined the chemical composition of the meat and the food supplied to the buffaloes, referencing the standard methods of the Official Association of Analytical Chemists (AOAC). The fatty acid profile was also determined, with extraction according to the Folch technique and gas chromatography (GC), identifying saturated (SFA), unsat-urated (UFA): monounsaturated (MUFA) and polyunsaturated (PUFA) fatty acids present in the intramuscular fat. The average values in meat were 28.09% db, 71.91% moisture, 23.69% crude protein, 1.94% ethereal extract (chemical fat), and 1.23% ash. Regarding fatty acids, values of 18.59% SFA and 81.4% UFA were found, standing out within the latter 77.4% MUFA and 4% PUFA. Ratio n-3/PUFA/n-6 PUFA was 1:2. No significant differences in breeds and crosses were detected, concluding that buffalo meat is nutritionally healthy and productively profitable for the region.